Creative Products from Cassava Peel Waste to Be Delicious and Nutritious Snacks, Desa Sukamanah, Megamendung District, Bogor Regency - Yuppy Triwidatin; Yulianingsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
Starting from concerns about cassava skin waste and utilizing materials that are around, the villagers Sukamanah, Megamendung District, Bogor Regency, through this community service, dares to innovate by processing unused food ingredients into a type of product with high economic value. Cassava has long been used as food for the people of Indonesia. Especially in the land of Sunda, cassava has its own place on a par with rice. The tubers, which are usually used as food, are processed by boiling, frying and steaming. Usually the cassava that is to be processed is only targeted at the tubers, while the skin discarded because they are considered waste and can no longer be used. Through this activity, they are finally able to use cassava peels to become a light snack that is delicious to eat and has a sale value. Cassava skin is made into other processed products in the form of chips Crispy cassava skin from waste is made into delicious and nutritious snacks.